Relevance of the American College of Surgeons Oncology Group Z0011 Trial to breast cancer in the Australian setting. Issue 12 (December 2013) - Ngui, Nicholas K.; Elder, Elisabeth E.; Jayasinghe, Upali W.; French, James
Abstract Background: Conventional wisdom suggests that a patient with a positive sentinel node requires a completion axillary clearance to obtain full staging and durable regional control. However, this dictum has been challenged by the recent American College of Surgeons Oncology Group Z0011 Trial demonstrating that women with node‐positive breast cancer who underwent sentinel node biopsy only, and were treated with breast conserving surgery and radiation, had equivalent locoregional recurrence and survival rates to those who had a completion axillary clearance. The aim of our study was to determine what the clinical impact of the Z0011 findings might be if patients were managed according to the Z0011 criteria in an Australian teaching hospital setting. Methods: We performed a retrospective review, using prospectively collected data, of all female patients with breast cancer assessed at the Westmead Breast Cancer Institute in 2010 and identified the subgroup who would potentially have fulfilled all Z0011 criteria. The characteristics and management of this group were compared with node‐positive and to mastectomy patient subgroups. Results: A total of 280 patients with invasive breast cancer were identified. Twenty‐six patients satisfied all Z0011 criteria, representing 9.3% of all patients and 21.5% of node‐positive patients. Twenty‐two (84.6%) patients had a subsequent axillary clearance, with six (27.3%) having additional positive nodes. Conclusions: The Z0011 study is relevant to 9.3% of all breast cancer patients and 21.5% of node‐positive breast cancer patients treated in a major Australian teaching hospital.